PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING LEARNING TERHADAP HASIL BELAJAR SISWA SMA NURUL AMAL - Theriana, Ana (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2020)
The problem in this research was whether there is the effect of the Probing Prompting Learning model on student learning outcomes in the10thgradersof SMANurulAmal Palembang. The purpose of this study was to determine the influence of the Probing Prompting Learning model on student learning outcomes at SMA NurulAmal Palembang. The method used in this study was the experimental method using two classes, namely the experimental class, and the control class. Meanwhile, the data collection technique was done by tests, and documentation techniques, then the data were analyzed by the data analysis technique using t-test analysis. The results showed that the average value of the experimental class was more than 80.24 compared to the control class of 63.6 and the calculations resulted tcountedtableie, 7.02 â‰¥ 1.667 then Ho was rejected and Ha was accepted. In other words, there was the influence of the Probing Prompting Learning model on learning outcomes.